Community perceptions and governance of tree planting schemes in Ethiopia: Insights for sustainable ecological and socioeconomic outcomes - Tibebe Weldesemaet Yitbarek; John R. U. Wilson; Adrian Evans; Katharina Dehnen‐Schmutz (People and Nature)
Abstract Historically, tree planting was primarily implemented to achieve economic functions; more recently, environmental and social goals have also been emphasised. This is due to the realisation that schemes operate in a socioecological system; hence, understanding and fulfilling local social (community) interests are imperative. We conducted 13 focus group discussions and 40 interviews with communities at 13 Ethiopian tree‐planting scheme sites to evaluate their perceptions of the landscape challenges, scheme governance processes and to identify areas for improvement. We analysed the survey responses qualitatively and scored the level of community satisfaction with the governance of each scheme. The results indicated that the communities understood and felt the impact of the landscape challenges while being optimistic about tree‐planting schemes’ potential to avert these issues. However, the communities differed markedly in their satisfaction with the scheme's governance, indicating that the degree to which schemes met their goals was related to the community's satisfactory engagement. Most respondents discussed issues about proper community consultation, engagement, institutionalisation and capacity building, starting from the input phase to the scheme governance process. We concluded that communities’ perceptions are valuable at all scheme phases and should be employed to improve a scheme's governance, outputs and impacts. We hope the results will help to encourage local communities’ participation in steering and refining the governance of inclusive and appealing tree‐planting schemes with sustainable ecological and socioeconomic outcomes. Read the free Plain Language Summary for this article on the Journal blog.